2009
DOI: 10.1017/s0967199409990189
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in CD9 content and reorganization of microvilli may contribute to the oolemma block to sperm penetration during fertilization of mouse oocyte

Abstract: Tetraspanin CD9 is the only protein of the oocyte membrane (oolemma) known to be required for the fusion of gametes during fertilization in the mouse. Using electron microscopy and immunostaining we examined the differences in localization of CD9 between ovulated oocytes, zygotes and parthenogenetically activated eggs (parthenogenotes). Changes in ultrastructure of oolemma, which take place in oocytes after fertilization or artificial activation, were also assessed. We demonstrated that after fertilization the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Similarly, in our study, Plac1 enriched on the cell membrane, presumably via its ZP-like domain, and Plac1 knockdown caused the abnormal distribution of cortical microvillus. As an irregular microvillar shape and organization contribute to the abnormal fertilization of mouse oocytes (20)(21)(22), this could account, in part, for the decreased fertilization after Plac1 knockdown. In contrast, Plac1 knockdown significantly decreased Akt phosphorylation, as Akt is well known to play an important role in the mitotic cell cycle and in meiosis (23,24), and we also showed that Akt inhibition significantly perturbed meiosis progression (reduced MII rate).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in our study, Plac1 enriched on the cell membrane, presumably via its ZP-like domain, and Plac1 knockdown caused the abnormal distribution of cortical microvillus. As an irregular microvillar shape and organization contribute to the abnormal fertilization of mouse oocytes (20)(21)(22), this could account, in part, for the decreased fertilization after Plac1 knockdown. In contrast, Plac1 knockdown significantly decreased Akt phosphorylation, as Akt is well known to play an important role in the mitotic cell cycle and in meiosis (23,24), and we also showed that Akt inhibition significantly perturbed meiosis progression (reduced MII rate).…”
Section: Discussionmentioning
confidence: 99%
“…Is CD9 directly involved in the microvillar architecture? A hint of its direct structural role was already provided in Cd9 null oocytes, where numerous alterations (length, thickness and density) in microvillus-like structures were noted [ 32 , 34 ]. Similarly, we observed that CD9 knockdown causes alterations of microvillus-like structures at the dorsal part of MDA cells, which resulted in the appearance of tiny dorsal ruffles.…”
Section: Discussionmentioning
confidence: 99%
“…The modelling suggests a disordered highly flexible region without strong preference for secondary structure. However, the remaining part of the extracellular domain is stabilized by two disulphide bridges, and the domain is involved in a closed/open conformation change [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Follow-up association of tetraspanins with membrane-curving proteins or lipids, or different tetraspanins with abilities to bind these molecules, could influence the curvature of the cell membrane and formation of various tubular structures (e.g., microvilli) associated with cell adhesion and intercellular communication [ 25 ]. The changes of microvilli distribution and their CD9 content were proposed to be responsible for the development of the oocyte membrane block to sperm penetration [ 26 ] and female infertility of CD81-deficient mice due to less outward curvature of the oolema was also predicted [ 25 ]. The membrane tubular structures formation could be regulated by associations of tetraspanins with actin cytoskeleton via ERM proteins [ 25 ].…”
Section: Introductionmentioning
confidence: 99%